Influence of the local universe on weak gravitational lensing surveys - Reischke, Robert; Schäfer, Björn Malte (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. Observations of the large-scale structure (LSS) implicitly assume an ideal Friedmann-Lemaitre-Robertson-Walker (FLRW) observer with the ambient struc
Gesehen am 03.06.2019